2020
DOI: 10.1186/s12912-020-00480-4
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and midwifery students’ experiences and perception of their clinical learning environment in Malawi: a mixed-method study

Abstract: Background The clinical learning environment is an important part of the nursing and midwifery training as it helps students to integrate theory into clinical practice. However, not all clinical learning environments foster positive learning. This study aimed to assess the student nurses and midwives’ experiences and perception of the clinical learning environment in Malawi. Methods A concurrent triangulation mixed methods research design was used to collect data from nursing and midwifery students. Quantita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 42 publications
9
47
2
8
Order By: Relevance
“…Generally, the study findings revealed showed some congruence with other studies internationally Abdulmutalib et al [12], Bäck et al, [13], Mbakaya et al [14] and locally in findings of Adjei et al [15] that students' exposure to clinical practicum have impact on students learning outcome. Positively in our study, majority of the study participants expressed some satisfaction with the clinical exposure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Generally, the study findings revealed showed some congruence with other studies internationally Abdulmutalib et al [12], Bäck et al, [13], Mbakaya et al [14] and locally in findings of Adjei et al [15] that students' exposure to clinical practicum have impact on students learning outcome. Positively in our study, majority of the study participants expressed some satisfaction with the clinical exposure.…”
Section: Discussionsupporting
confidence: 83%
“…From the stories shared by the participants, they are not given the chance to acquire skills and competencies per the set objectives for practicum hence, are not fully prepared and are also not supervised to learn or acquire clinical standard skills and competencies. These findings showed some contradictions with the findings of [6,13,14] which revealed that, there are well-planned practicum activities by the nurses whenever students are on practicum. Also, there is an effective clinical practice of students under supervision and that promotes learning and helped students to achieve learning outcomes and competencies through the diversity of learning opportunities but this was not seen in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…This involves observing the physical space, the psychosocial interactions, culture of the workplace, and the learning and teaching factors. [23,24] The connection which the students reported they made between theoretical and practical nursing knowledge gained from their university studies and observership, aligns with what Mezirow [25] described as a transformative learning experience, or as Chick and Meleis [26] identified as a "passage", where the student moves from one state to another, that is from a nursing student to a professional nursing student.…”
Section: Discussionsupporting
confidence: 58%
“…Looking at more recent, similar research findings (Motsaanaka et al 2020 ), the findings of this research are still relevant. More recent studies still report that students need emotional, cognitive and systems support such as personal attention, care, guidance to gain confidence and socialisation in nursing (Bazrafkan & Kalyani 2018 ; Hosseinabadi et al 2020 ; Hugo, Botma & Raubenheimer 2018 ; Kgafele, Coetzee & Heyns 2015 ; Mbakaya et al 2020 ; Mekgoe et al 2019 ), whilst the current study offers valuable findings and recommendations that can add to the body of knowledge on this important topic.…”
Section: Methodsmentioning
confidence: 72%
“…At the time of the research, the first author’s own experience as a professional nurse in a PHC clinic also confirmed the need for this research. Whilst more recent research has also been reported at the international level and in the African context on the learning experiences of nursing students during placement at PHC clinics, support for nursing students during clinical placement in PHC remains lacking (Fröberg et al 2018 ; Mackey et al 2018 ; Mbakaya et al 2020 ). There is thus an ongoing need for research to explore and describe nursing students’ experience of clinical placement in PHC clinics, in this case in a province in SA, and to apply the findings to recommend strategies for support to strengthen students’ resilience during challenging clinical situations.…”
Section: Introductionmentioning
confidence: 99%